Elevated plasma neurofilament light predicts a faster rate of cognitive decline over 5 years in participants with objectively‐defined subtle cognitive decline and MCI. Issue 10 (15th April 2021) - Bangen, Katherine J.; Thomas, Kelsey R.; Weigand, Alexandra J.; Edmonds, Emily C.; Clark, Alexandra L.; Solders, Seraphina; Delano‐Wood, Lisa; Galasko, Douglas R.; Bondi, Mark W.; ,
Abstract: Introduction: Neurofilament light (NFL) reflects neuroaxonal damage and is implicated in mild cognitive impairment (MCI) and Alzheimer's disease (AD). Little is known about NFL in pre‐MCI stages, such as in individuals with objectively‐defined subtle cognitive decline (Obj‐SCD). Methods: Two hundred ninety‐four participants from the Alzheimer's Disease Neuroimaging Initiative (ADNI) underwent baseline blood draw and serial neuropsychological testing over 5 years of follow‐up. Results: Individuals with Obj‐SCD and MCI showed elevated baseline plasma NFL relative to the cognitively normal (CN) group. Across the sample, elevated NFL predicted faster rate of cognitive and functional decline. Within the Obj‐SCD and MCI groups, higher NFL levels predicted faster rate of decline in memory and preclinical AD composite score compared to the CN group. Discussion: Findings demonstrate the utility of plasma NFL as a biomarker of early AD‐related changes, and provide support for the use of Obj‐SCD criteria in clinical research to better capture subtle cognitive changes.